Prophétie féminine et autorité institutionnelle dans l’État de Savoie à l’époque moderne: hypothèses de recherche - Elisabetta Lurgo (Genre & Histoire)
Historians of Renaissance Italy have studied groups of women who were seen as prophetic visionaries in princely courts. These « courtly prophetesses » have been studied as part of the princes’ court, medium between lords and their subjects, thanks to their visions and prophecies. In my article I set out to analyse the role of female prophecy and vision in the Savoy Estate, between the XVIth and XVIIIth centuries: the ultimate aim is to try and underline the relationship between prophetical charisma and institutional authority in the early modern era. The starting point, therefore, is the representation and definition of power, understood as a constant interpenetration between aristocratic and court rituals and local practices.